2000
DOI: 10.1002/1098-2337(2000)26:4<309::aid-ab3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive-age women are overrepresented among perpetrators of husband killing

Abstract: When a woman kills her husband, it is almost always an unplanned action of self‐defense against a battering husband or a last‐ditch attempt to survive a batterer's tyranny. Younger, reproductive‐age women are battered and killed by husbands at higher rates than are older, postreproductive‐age women. Because husband killing occurs in the context of self‐defense or as a last‐ditch effort to survive, reproductive‐age women should kill their husbands at higher rates than do postreproductive‐age women. I used a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
3
12
1
Order By: Relevance
“…For example, the mean age of women who are at least 15 years older than the man is 54, but their ages range from 36 to 82; the mean age of men when the woman is at least 15 years older is 33, but the range is 20 to 52. Previous studies have also reported that reproductive age women (women who are less than 45 years old) are overrepresented among offenders and victims of spousal homicides (Shackelford, 2000;Shackelford et al, 2000). An analysis of the present data confirms these results: the woman was less than 45 years in 82.9% of women-offender IPHs, and in 82.8% of women-victim IPHs.…”
Section: Intimate Partner Homicide Datasupporting
confidence: 78%
See 4 more Smart Citations
“…For example, the mean age of women who are at least 15 years older than the man is 54, but their ages range from 36 to 82; the mean age of men when the woman is at least 15 years older is 33, but the range is 20 to 52. Previous studies have also reported that reproductive age women (women who are less than 45 years old) are overrepresented among offenders and victims of spousal homicides (Shackelford, 2000;Shackelford et al, 2000). An analysis of the present data confirms these results: the woman was less than 45 years in 82.9% of women-offender IPHs, and in 82.8% of women-victim IPHs.…”
Section: Intimate Partner Homicide Datasupporting
confidence: 78%
“…This study first documents that the association between extreme age discrepancy and elevated homicide risk occurs among all heterosexual intimate couples, not only cohabiting married or common-law couples. Using a Chicago dataset that includes all heterosexual intimate partner homicides, this analysis replicates national level findings for cohabiting legal spouses and common-law spouses (Mercy & Saltzman, 1989;Shackelford, 2000Shackelford, , 2001aShackelford, , 2001bShackelford et al, 2000). Specifically, couples in which the woman is older by at least 10 years or in which the man is older by at least 16 years have substantially higher risk of IPH, compared to a Rates for the three categories, women 10 to 12 years older, women 13 to 15 years older and women more than 15 years older, are based on fewer than 10 cases (8, 5, and 8, respectively); see Table 6.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations